Istishab: Dynamics of Islamic Legal Construction and Its Significance in Digital Era Fiqh Muamalah Transformation - Ahmad Yusdi Gozaly; Siti Nuraeni; Agung Hari Wibowo; Amalia Amalia (STAI Al-Mas'udiyah, 2025)
This research aims to investigate the position of istishab in the epistemological hierarchy of Islamic law, explore its operationalization mechanisms in the istinbat process, and analyze its impact on the evolution of contemporary fiqh muamalah. The methodology employed is library research with a descriptive-analytical approach to classical and modern literature on istishab. Research findings indicate that istishab functions as a mechanism for preserving the legal status quo until evidence is found that changes it. Despite divergent scholarly opinions regarding its legal authority, the majority of scholars from the Malikiyyah, Shafi'iyyah, and Hanabilah schools acknowledge the validity of istishab as a legal proof. In the context of digital-era fiqh muamalah, istishab makes significant contributions to Islamic financial product innovation, digital economic regulation formulation, and business conflict resolution. The maxims al-yaqin la yuzalu bi al-syak (certainty is not removed by doubt) and al-ashl fi al-asyya' al-ibahah (the original state of things is permissibility) serve as the foundation for implementing istishab in contemporary muamalah innovations. In conclusion, istishab has high relevance as an instrument for Islamic law adaptation to civilizational dynamics, particularly in the muamalah domain experiencing accelerative transformation.